Efeito do corte no estádio vegetativo e de épocas de colheita sobre o rendimento e qualidade das sementes de Macroptilium Lathyroides (L.) Urb - Ferreira, Otoniel Geter Lauz (2002)
In a hidromorphic soil of EETB/EMBRAPA - CPACT, at Capão do Leão, RS, Brasil, the effects of cutting during vegetative growth and seven seed harvesting dates at weekly intervals, on components of seed yield production and seed quality of Macroptilium lathyroides (L.) Urb. were evaluated. First harvest was wade on April 05, 2001, when first ripe legumes appeared from second flowering. Last seed harvest was made in May 16, 2001. A complete randomized block design with three replications was used. Cutting during vegetative growth stage increased the seed yield components. With advancing harvesting dates an increase occurs in seed yield components. Number of branchings, flowers and legumes/area, number of seeds/plant and 1000 seeds weight are inefficient to predict of seed yield. Seeds moisture remains high during harvesting dates. Maximum germination, vigor and 1000 seeds weight are reached when first ripe legumes appeared. Cutting in vegetative growth stage results in seed of higher vigor and moisture. Cutting in vegetative growth stage and seed harvesting dates did not influence seed yield.